Activity estimation in radioimmunotherapy using magnetic nanoparticles - Rasaneh, Samira; Rajabi, Hossein; Johari Daha, Fariba (Chinese Journal of Cancer Research, 2015)
Objective: Estimation of activity accumulated in tumor and organs is very important in predicting the response of radiopharmaceuticals treatment. In this study, we synthesized 177Lutetium (177Lu)-trastuzumab-iron oxide nanoparticles as a double radiopharmaceutical agent for treatment and better estimation of organ activity in a new way by magnetic resonance imaging (MRI). Methods: 177Lu-trastuzumab-iron oxide nanoparticles were synthesized and all the quality control tests such as labeling yield, nanoparticle size determination, stability in buffer and blood serum up to 4 d, immunoreactivity and biodistribution in normal mice were determined. In mice bearing breast tumor, liver and tumor activities were calculated with three methods: single photon emission computed tomography (SPECT), MRI and organ extraction, which were compared with each other. Results: The good results of quality control tests (labeling yield: 61%±2%, mean nanoparticle hydrodynamic size: 41±15 nm, stability in buffer: 86%±5%, stability in blood serum: 80%±3%, immunoreactivity: 80%±2%) indicated that 177Lu-trastuzumab-iron oxide nanoparticles could be used as a double radiopharmaceutical agent in mice bearing tumor. Results showed that 177Lu-trastuzumab-iron oxide nanoparticles with MRI had the ability to measure organ activities more accurate than SPECT. Conclusions: Co-conjugating radiopharmaceutical to MRI contrast agents such as iron oxide nanoparticles may be a good way for better dosimetry in nuclear medicine treatment.